Streptomycin Sulfate–Loaded Niosomes Enables Increased Antimicrobial and Anti-Biofilm Activities - Mansouri, Maryam; Khayam, Nazanin; Jamshidifar, Elham; Pourseif, Tara; Kianian, Sepideh; Mirzaie, Amir; Akbarzadeh, Iman; Ren, Qun (Frontiers in Bioengineering and Biotechnology, 2021)
One of the antibiotics used to treat infections is streptomycin sulfate that inhibits both Gram-negative and -positive bacteria. Nanoparticles are suitable carriers for the direct delivery and release of drug agents to infected locations. Niosomes are one of the new drug delivery systems that have received much attention today due to their excellent biofilm penetration property and controlled release. In this study, niosomes containing streptomycin sulfate were prepared by using the thin layer hydration method and optimized based on the size, polydispersity index (PDI), and encapsulation efficiency (EE%) characteristics. It was found that the Span 60-to-Tween 60 ratio of 1.5 and the surfactant-to-cholesterol ratio of 1.02 led to an optimum formulation with a minimum of size, low PDI, and maximum of EE of 97.8 nm, 0.27, and 86.7%, respectively. The drug release investigation showed that 50.0 ± 1.2% of streptomycin sulfate was released from the niosome in 24 h and reached 66.4 ± 1.3% by the end of 72 h. Two-month stability studies at 25° and 4°C showed more acceptable stability of samples kept at 4°C. Consequently, antimicrobial and anti-biofilm activities of streptomycin sulfate–loaded niosomes against Staphylococcus aureus, Escherichia coli, and Pseudomonas aeruginosa were found significantly higher than those of free drug, and the minimum inhibitory concentration values decreased 4- to 8-fold. Furthermore, niosome-encapsulated streptomycin up to 1,500 μg/ml exhibited negligible cytotoxicity against the human foreskin fibroblasts cell line, whereas the free drug exhibited slight cytotoxicity at this concentration. Desired physical characteristics and low toxicity of niosomal nano-carriers containing streptomycin sulfate made them a demanded candidate for the treatment of current bacterial infections and biofilms.